Detection and residence time of bisphosphonates in bone of horses. (January 2022) - Knych, Heather K.; Janes, Jennifer; Kennedy, Laura; McKemie, Daniel S.; Arthur, Rick M.; Samol, Monika A.; Uzal, Francisco A.; Scollay, Mary
Bisphosphonates are potent anti-resorptive agents that have the potential to adversely affect bone healing in equine athletes, and normal bone adaption in young racehorses. A concern exists that bisphosphonate inhibition of normal bone metabolism could lead to increased bone fractures during high-intensity exercise. We found only a single report describing concentrations of tiludronate in the bone of horses, and no studies describing clodronate. Knowledge of the residence time in bone could allow for a better understanding of the long-term effects of these compounds. Our objectives were to develop a method for detection of bisphosphonates in bone and add to the limited information available regarding the disposition of these drugs in the bone of horses. Two horses received clodronate and 2 tiludronate disodium. Postmortem collection of bones and teeth occurred either 4 or 30 d post drug administration. Additionally, postmortem blood, synovial fluid, aqueous humor, and bone samples from racehorses with various histories of bisphosphonate administration were collected, and concentrations determined using the developed LC-MS/MS method. Bisphosphonates were detected in bones and teeth tested at 4 and 30 d. In a postmortem sample, clodronate was detected in bone from a horse with reported administration 18 mo prior; clodronate was not detected in other sample types collected from this horse. Bisphosphonates reside in bone for extended periods of time, which could lead to potential long-term effects, increasing the potential for bone fractures in young and/or athletic horses.